Right to assisted reproductive technology: Overcoming infertility in low-resource countries - Inhorn, Marcia C (International journal of gynecology and obstetrics, 2009)
Abstract This article examines the high prevalence of primary and secondary infertility in low-resource countries. Provision of assisted reproductive technology (ART) to overcome both female and male infertility is in line with the reproductive rights agenda developed at the International Conference on Population and Development (ICPD) in Cairo 15 years ago. In addition to the right to control fertility, reproductive rights must encompass the right to facilitate fertility when fertility is threatened. Facilitation of fertility may require resort to ART, among both men and women. Egypt is highlighted as a positive example of progress in this regard.